2008
DOI: 10.1007/s00213-008-1099-6
|View full text |Cite
|
Sign up to set email alerts
|

Affective neuroscience of pleasure: reward in humans and animals

Abstract: Introduction Pleasure and reward are generated by brain circuits that are largely shared between humans and other animals. Discussion Here, we survey some fundamental topics regarding pleasure mechanisms and explicitly compare humans and animals. Conclusion Topics surveyed include liking, wanting, and learning components of reward; brain coding versus brain causing of reward; subjective pleasure versus objective hedonic reactions; roles of orbitofrontal cortex and related cortex regions; subcortical hedonic ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
807
4
21

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,061 publications
(874 citation statements)
references
References 208 publications
(258 reference statements)
18
807
4
21
Order By: Relevance
“…From neuroscientists' point of view, palatability corresponds to the 'liking' or hedonic component of the brain reward system (Berridge, 1996), which deals with affective responses to the food and induces pleasure (Berridge and Kringelbach, 2008).…”
Section: Sensory Characteristics: a Way To Get Pleasurementioning
confidence: 99%
“…From neuroscientists' point of view, palatability corresponds to the 'liking' or hedonic component of the brain reward system (Berridge, 1996), which deals with affective responses to the food and induces pleasure (Berridge and Kringelbach, 2008).…”
Section: Sensory Characteristics: a Way To Get Pleasurementioning
confidence: 99%
“…Thus, it has been found that the esthetic experience involves a widely distributed circuit with greater activation for beautiful stimuli in anterior cingulate gyrus, dorsolateral and medial frontal cortices (Berridge and Kringelbach, 2008;Breiter et al, 2001;Di Dio et al, 2011;Kirk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the relation between neural and behavioural reward responses to reward may seem straightforward, the behavioural and neural parameters compared here may reflect different stages of reward processing. As described in the Introduction, reward processing can be viewed as involving three stages (Berridge & Kringelbach, 2008). First, reward anticipation , preceding the rewarding stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…As such, reward is pivotal for driving many human behaviours. Following this, different phases of reward functioning may be defined as distinct behaviours (Berridge & Kringelbach, 2008; Nawijn et al, 2015). Reward wanting is the anticipatory motivation towards obtaining the stimulus, whereas reward consumption is linked to the pleasure felt by obtaining the stimulus.…”
Section: Introductionmentioning
confidence: 99%